Overcoming tumor-mediated immunosuppression. (September 2014) - Schlößer, Hans Anton; Theurich, Sebastian; Shimabukuro-Vornhagen, Alexander; Holtick, Udo; Stippel, Dirk Ludger; Bergwelt-Baildon, Michael von
Mechanisms of tumor-mediated immunosuppression have been described for several solid and hematological tumors. Tumors inhibit immune responses by attraction of immunosuppressive lymphocytic populations, secretion of immunosuppressive cytokines or expression of surface molecules, which inhibit immune responses by induction of anergy or apoptosis in tumor-infiltrating lymphocytes. This tumor-mediated immunosuppression represents a major obstacle to many immunotherapeutic or conventional therapeutic approaches. In this review we discuss how tumor-mediated immunosuppression interferes with different immunotherapeutic approaches and then give an overview of strategies to overcome it. Particular emphasis is placed on agents or approaches already transferred into clinical settings. Finally the success of immune checkpoint inhibitors targeting CTLA-4 or the PD-1 pathway highlights the enormous therapeutic potential of an effective overcoming of tumor-mediated immunosuppression.